2021
DOI: 10.1002/pol.20210664
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide membranes enabled by covalent organic framework nanofibers for efficient reverse osmosis

Abstract: Polyamide reverse osmosis membranes are indispensable for the worldwide clean water supply. Incorporation of nanomaterials into polyamide separation layer provides an evident methodology to enhance the water flux. However, the desalination performance would be compromised by the inadequate com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Covalent organic frameworks (COFs) are a class of crystalline polymers with tunable and permanent pores, atomically ordered pore structures, and high porosity, constructed by the covalent linkage of organic building blocks (or monomers) based on reticular chemistry 11 14 . The diversity of organic building blocks endows COFs with exceptional structural designability, enabling the customization of the pore size and the functionality at molecular level 15 18 . For instance, choosing appropriate monomers, the COF pores can be manipulated to separate molecules based on size, shape, or charge 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are a class of crystalline polymers with tunable and permanent pores, atomically ordered pore structures, and high porosity, constructed by the covalent linkage of organic building blocks (or monomers) based on reticular chemistry 11 14 . The diversity of organic building blocks endows COFs with exceptional structural designability, enabling the customization of the pore size and the functionality at molecular level 15 18 . For instance, choosing appropriate monomers, the COF pores can be manipulated to separate molecules based on size, shape, or charge 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The measurement results demonstrated that the liposomes-integrated membranes, produced through either the conventional blending or spray-assisted strategies, exhibited smaller contact angles compared to the control membrane, indicating the formation of highly wettable surfaces. Wenzel's theory tightly associates surface hydrophilicity with surface roughness, stating that increased roughness can amplify hydrophilicity on an intrinsically hydrophilic surface (Yang et al 2022). Thus, the decreased contact angles observed in the BM-Conv and BM-Spray membranes (58.8°-60.6°) could be attributed to their rougher membrane surfaces, which facilitated the dispersion of water droplets.…”
Section: Surface Wettability Of Membranesmentioning
confidence: 98%